Characterisation of New Zealand Propolis from Different Regions Based on Its Volatile Organic Compounds - Mountford-McAuley R; Robertson A; Taylor M; Clavijo McCormick A (MDPI (Basel, Switzerland), 2024)
Propolis is a bee product mainly consisting of plant resins and is used by bees to maintain the structural integrity of the colony. Propolis is known to contribute to bee health via its antimicrobial activity and is a valued product for human use owing to its nutritional and medicinal properties. Propolis is often characterised into seven categories depending on the resin source. New Zealand propolis is typically assumed as being poplar-type propolis, but few studies have chemically characterised New Zealand propolis to confirm or reject this assumption. Here, for the first time, we characterise propolis originating from different regions in New Zealand based on its volatile organic compounds, using gas chromatography coupled with mass spectrometry (GC-MS). To support this characterisation, we also collected and analysed resin samples from a variety of resin-producing plants (both native to New Zealand and introduced). Our findings suggest that bees mainly use poplar as a resin source, but also utilize native plant species to produce propolis. While regional variation did not allow for clear separation between samples, some patterns emerged, with samples from some regions having more chemical complexity and a higher contribution from native species (as suggested by a higher number of compounds unique to native species resin). Further studies are needed to accurately identify the botanical sources contributing to these samples. It may be also of interest to explore the biological activity of regional propolis samples and their potential nutritional or medicinal benefits.
Keywords: biological activity; native plants; poplar; resin; terpenes; volatile organic compounds; Propolis; New Zealand; Volatile Organic Compounds; Gas Chromatography-Mass Spectrometry; Bees; Animals; Resins, Plant